Feminism in Geni Jora by Abidah Khaliqy and Menongkah Lumrah by Azmah Nordin: a comparative study - Asmiaty Amat (Dewan Bahasa dan Pustaka, 2007)
In actuality, the question of women's emancipation in the literature of Malaysia and Indonesia was first started by men. If in Malaysia it was through Hikayat Faridah Hanum (1925/26) by Syed Syeikh AI-Hadi, in Indonesia it was brought forth by Sutan Takdir Alisyahbana through his work Layar Terkembang (1937). However, the literary scenarios of the two countries, which was dominated by male writers, placed the female characters on the sidelines and they were depicted as being of inferior types. Thus the emergence of women writers, who are said to be more understanding and able to speak about women's feelings and experiences.